Utilization of Focus Groups to Design Curricula to Teach 3D/4D Technology - (:unkn) unknown (My University, 2013)
Diagnostic medical sonography is a tool utilized daily in the medical field. Currently there is a trend of moving from 2D technologies to newer, advanced 3D/4D technologies. The issue involved with adding 3D/4D technology to the echocardiography exam is how to best teach the sonographers how to become comfortable with using the newer technology. The aim of this study was to use focus groups and grounded theory as tools for curriculum development to teach cardiac sonographers 3D/4D technology to calculate left ventricular volume. The setting for this study was an academic medical center in which eight cardiac sonographers were recruited to learn how to utilize 3D technology to calculate left ventricular volumes. The sonographers were asked to participate in two focus groups, online learning modules, hands-on practice sessions, and a final hands-on session with a data set to test the effectiveness of the final educational material. The methodology utilized for this study was qualitative, with audio taped interviews in focus groups and videotaped hands-on observation of 3D phantom scanning. Grounded theory was utilized to evaluate the data collected and to develop curricula to teach sonographers how to measure left ventricular volumes. Results indicate that in order to have successful implementation of a curriculum into the laboratory, specific educational materials and hands-on practice sessions should be provided to enhance learning and understanding of 3D technology. Sonographers participating in this study defined barriers to learning 3D technology as not enough time, positioning of equipment in examination rooms, too many different uses of 3D technology, and 3D technology “experience gap.” Findings indicate that focus groups serve as a mechanism for identifying barriers to learning and designing an effective curriculum for teaching sonographers how to measure left ventricular volumes.
Keywords: Echocardiography; Focus Group; Grounded Theory; Left Ventricular Volume